Kajian KAJIAN USAHA BARU ASPEK PEMASARAN, PRODUKSI, KEUANGAN, DAN MAKRO EKONOMI : (STUDI DAN SURVEY PADA PDAM TIRTAMARTA YOGYAKARTA) - Kuswantoro, Ferri; Dwiwinarno , Titop; Hasthoro , Handoko; Hasanah, Erni; Nurwiyanta, Nurwiyanta; Burhanudin, Burhanudin; Lokananta, Robid; Mardianto, Toni (Fakultas Ekonomi Universitas Balikpapan, 2023)
ABSTRACT Along with the increasing need for mineral water, regional company Tirtamarta Yogyakarta will make a break through by developing diversification of products branded